2022
DOI: 10.1029/2021jb023488
|View full text |Cite
|
Sign up to set email alerts
|

Slab Geometry and Upper Mantle Flow Patterns in the Central Mediterranean From 3D Anisotropic P‐Wave Tomography

Abstract: The Central Mediterranean region is an active plate margin characterized by the presence of both oceanic and continental lithosphere. The recent tectonic history is marked by intense seismic and volcanic activity triggered by episodes of continental collision and slab rollback leading to the formation of mountain ranges and extensional basins (Faccenna et al., 2014). Our understanding of the structural heterogeneity and tectonic complexity of this region requires accurate imaging of the subsurface. For this re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 102 publications
3
19
0
Order By: Relevance
“…Wang & Zhao, 2021) and its forearc area (Z. Wang et al, 2022), northern Fennoscandia (Munzarová et al, 2018), Central Mediterranean (Rappisi et al, 2022), and Cascadia subduction zone (Liang et al, 2023). These studies have demonstrated that the tilting-axis anisotropy can reveal more complex 3-D mantle flow by reconciling the contradictory assumptions of azimuthal and radial anisotropies.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Wang & Zhao, 2021) and its forearc area (Z. Wang et al, 2022), northern Fennoscandia (Munzarová et al, 2018), Central Mediterranean (Rappisi et al, 2022), and Cascadia subduction zone (Liang et al, 2023). These studies have demonstrated that the tilting-axis anisotropy can reveal more complex 3-D mantle flow by reconciling the contradictory assumptions of azimuthal and radial anisotropies.…”
mentioning
confidence: 80%
“…Recently, a novel tomographic technique has been developed to reveal tilting‐axis anisotropy, with the HSA freely orientated in 3‐D space (Z. Wang & Zhao, 2021). So far, this type of techniques has successfully revealed the presence of tilting HSA beneath the Japanese region (Z. Wang & Zhao, 2021) and its forearc area (Z. Wang et al., 2022), northern Fennoscandia (Munzarová et al., 2018), Central Mediterranean (Rappisi et al., 2022), and Cascadia subduction zone (Liang et al., 2023). These studies have demonstrated that the tilting‐axis anisotropy can reveal more complex 3‐D mantle flow by reconciling the contradictory assumptions of azimuthal and radial anisotropies.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in models with trench-oblique mantle flow, larger differences in slab geometry have been reported (Chertova et al, 2018), as a response to more complex interactions between imposed and slab-induced mantle flows. The effect of trench-oblique mantle flow, although possible on Earth especially in areas with complex geometries (e.g., Mediterranean, Rappisi et al, 2022), was not addressed in our study. We can nevertheless anticipate that it may lead to more variability of along-strike slab geometry and in turn to more complex patterns of deformation of the upper plate.…”
Section: Slab Geometrymentioning
confidence: 97%
“…The obtained 3-D numerical simulation results (e.g., Confal et al, 2018;Faccenda & Capitanio, 2013) and seismic tomographic models (e.g., VanderBeek & Faccenda, 2021;Wang & Zhao, 2021) are more consistent with various geophysical observations. The tilting-axis anisotropic tomography has been applied to investigate the detailed 3-D anisotropic structures beneath Japan Wang & Zhao, 2021), Cascadia (Liang et al, 2023), Central Mediterranean (Rappisi et al, 2022), and Alaska (Liang et al, 2024), providing new insights into subduction dynamics. Xie et al (2023) took in account the morphology of the subducting Australian slab to constrain the 3-D isotropic P-wave velocity (Vp) structure under Java.…”
Section: Introductionmentioning
confidence: 99%